Empirical Loss Timescales of Slot Region Electrons due to Plasmaspheric Hiss Based on Van Allen Probes Observations. Issue 4 (23rd April 2021) - Zhu, Qi; Cao, Xing; Gu, Xudong; Ni, Binbin; Xiang, Zheng; Fu, Song; Summers, Danny; Hua, Man; Lou, Yuequn; Ma, Xin; Guo, Yingjie; Guo, Deyu; et al.
Abstract: Based on Van Allen Probes observations, in this study we perform a statistical analysis of the spectral intensities of plasmaspheric hiss at L‐shells of 1.8–3.0 in the slot region. Our results show that slot region hiss power intensifies with a strong day‐night asymmetry as the level of substorm activity or L‐shell increases. Using the statistical spectral profiles of plasmaspheric hiss, we calculate the drift‐ and bounce‐averaged electron pitch angle diffusion coefficients and subsequently obtain the resultant electron loss timescales through 1‐D Fokker‐Planck simulations. We find that slot region electron loss timescales vary significantly from <1 day to several years, showing a strong dependence on electron energy, L‐shell and substorm activity. We also construct an empirical model of slot region electron loss timescales due to scattering by plasmaspheric hiss, which agrees well with the 1‐D simulation results and can be readily used in modeling the dynamics of slot region electrons. Key Points: We perform a statistical analysis of the global distribution of hiss wave spectral intensities in the slot region The drift‐ and bounce‐averaged pitch angle diffusion coefficients of slot region electrons are calculated We develop an empirical model of slot region electron loss timescales due to plasmaspheric hiss